2019
DOI: 10.2965/jwet.19-073
|View full text |Cite
|
Sign up to set email alerts
|

Isomer-Specific Determination of Polychlorinated Naphthalenes in Landfill Leachates by Gas Chromatography/High-Resolution Mass Spectrometry

Abstract: As environmental contamination resulting from the release of polychlorinated naphthalenes (PCNs) from landfills is of concern, methods are required to quantify PCNs in landfill leachates. In this study, an isomer-specific analytical method for the determination of PCNs in leachate samples was developed using gas chromatography/high-resolution mass spectrometry. The leachate samples were flocculated and the flocks were extracted using Dean-Stark Soxhlet extraction. The sample extracts were cleaned up automatica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In addition, various results have been reported regarding their presence in the atmosphere, sediments, aquatic and terrestrial organisms, and biota in and outside the polar region [5]. However, few reports have examined the state of PCN concentrations in leachate from landfills where PCN-containing products might have been discarded [14]. Few investigations have been performed because of the need for a complex analytical method that must cover all PCN isomers as target analytes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, various results have been reported regarding their presence in the atmosphere, sediments, aquatic and terrestrial organisms, and biota in and outside the polar region [5]. However, few reports have examined the state of PCN concentrations in leachate from landfills where PCN-containing products might have been discarded [14]. Few investigations have been performed because of the need for a complex analytical method that must cover all PCN isomers as target analytes.…”
Section: Introductionmentioning
confidence: 99%
“…Few investigations have been performed because of the need for a complex analytical method that must cover all PCN isomers as target analytes. Our previous report suggested that PCNs listed as POPs in leachate at the final disposal site could be determined with the same pretreatment as for dioxin analysis [14]. In the previous research, DB-5 ms or (5%-Phenyl)-methylpolysiloxane-based similar non-polar capillary column for which the elution behavior of PCNs in GC-HRMS analysis was known [2,15,16] was applied, but these column is not commonly used in dioxin analysis [17].…”
Section: Introductionmentioning
confidence: 99%